My Thoughts Of PPM By Maimunah Kadir, Acting President (9.12.2014-14.4.2014) - Kadir, Maimunah (2015)
On 9th December 2014 PPM Council was shocked with the sudden passing away of our beloved President, Assoc. Professor Dr. Mohd Sharif Mohd Saad. As Vice President 1, I was naturally very close to our late President and either of us will call each other to discuss about matters regarding PPM. Without him we were in a state of shock for almost a week. Inna Lillahi wa inna ilayhi raji'un. Is a part of a verse from the Qur'an whith translates to "We surely belong to Allah and to Him we shall return. The phrase is recited by Muslims when a person experiences a tragedy in life, especially upon hearing news that a person has died.